The Effectiveness of the Doing Knowledge Model in International Educational Technology Classrooms - Dewi, Utari; Kristanto, Andi (Journal of Education Technology, 2025)
This research is motivated by the lack of relevant and applicable approaches in developing graphic media that hinder the competitiveness of global higher education. This study aims to examine the effectiveness of the doing knowledge learning model in improving the quality of lectures in the international class pilot of the Education Technology Study Program which has been internationally accredited. This type of research is experimental research that uses a quantitative approach with a non-equivalent pretest and posttest control group design method. The research subjects were 70 students. Data collection techniques were carried out by observation, interviews and questionnaires. The analysis method used includes quantitative descriptive analysis using t-test with a focus on project achievement as the main indicator of the success of the learning model. The results showed a significant difference between the experimental group and the control group. The average post-test of the experimental group reached 84.50, while the control group only reached 69.88, with a difference of 17.625 points. Thus, the results indicate that the doing knowledge model is effective in supporting project-based learning. The implication of this research is that it can increase the understanding of the implementation of the doing knowledge learning model to increase students' participation, concept understanding and critical thinking skills in international classes. Thus this study recommends the application of the doing knowladge model in media production-based courses and further development to increase the relevance of learning in the era of globalization of education.